2021
DOI: 10.34007/jehss.v4i2.801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership Style, Work Environment and Performance Benefits on Employee Performance in BP3TKI Office, Indonesia using Statistical Method

Abstract: This study aims to determine the effect of leadership style, work environment and performance benefits on employee performance at the Service Office for Placement and Protection of Indonesian Migrant Workers (BP3TKI) Medan. The effect of these variables on employee performance was studied using statistical analysis. The sampling technique used in this study is saturated sampling. Scaled surveys has been done by 116 employees of Service Office for Placement and Protection of Indonesian Migrant Workers (BP3TKI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The hypothesis of this research indicated that the workplace environment had a significant impact on shaping the performance of employees. A lot of research in the past had evaluated the similar kind of relationships in which changing environments and the factors of environments of workplace had significant contribution toward the job performance of employees (68). For instance, the work in (10) stated that with an increase in per unit variance for physical and behavioral environmental factors, employee's performance was increased which supported our argument.…”
Section: Discussionsupporting
confidence: 63%
“…The hypothesis of this research indicated that the workplace environment had a significant impact on shaping the performance of employees. A lot of research in the past had evaluated the similar kind of relationships in which changing environments and the factors of environments of workplace had significant contribution toward the job performance of employees (68). For instance, the work in (10) stated that with an increase in per unit variance for physical and behavioral environmental factors, employee's performance was increased which supported our argument.…”
Section: Discussionsupporting
confidence: 63%